2018
DOI: 10.22435/vektorp.v12i1.229
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Karakteristik Kontainer dengan Keberadaan Jentik Aedes aegypti pada Kejadian Luar Biasa Demam Berdarah Dengue : Studi Kasus di Kabupaten Ogan Komering Ulu

Abstract: Abstract Dengue hemorrhagic fever (DHF) is an infectious arboviral disease transmitted by Aedesmosquitoes. DHF is a public health importance in Indonesia which cause outbreaks inendemic areas. Dengue infection could be fatal if it is not immediately addressed. InJanuary 2016, the dengue outbreak occurred in the Sekarjaya community health center(CHC) working area, Ogan Komering Ulu district leading to one fatal case. A post-outbreakinvestigation was employed to observe the presence of the Aedes immature s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
5
0
4
Order By: Relevance
“…Research conducted by Santoso et al (2018) suggested that the level of larvae density (density figure) was categorized in the high density category with House Index (HI) = 46%, Container Index (CI)=21%, Pupa Index (PI) = 6%, and Bruteau Index (BI) = 79. .…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted by Santoso et al (2018) suggested that the level of larvae density (density figure) was categorized in the high density category with House Index (HI) = 46%, Container Index (CI)=21%, Pupa Index (PI) = 6%, and Bruteau Index (BI) = 79. .…”
Section: Discussionmentioning
confidence: 99%
“…This statement is supported by research which states that the Ae. Aegypti can thrive in all types of water, both clean and polluted water [22].…”
Section: Relationship Between Water Reservoir With Dhf Incidencementioning
confidence: 99%
“…Hal ini karena ukuran bak yang terlalu besar atau justru ember yang terlalu kecil sehingga penduduk tidak membuat penutup untuk jenis kontainer ini. (9) Kondisi kontainer yang terbuka menjadikan nyamuk lebih mudah untuk masuk dan berkembang biak pada tempat penampungan air. Hal tersebut sama halnya dengan tempat penampungan air yang tidak ditutup dengan sempurna atau kurang rapat.…”
Section: Pembahasanunclassified
“…Penyakit DBD selalu menjadi penyakit endemik dan menjadi masalah utama sampai saat ini. (1) Potensi cuaca yang sangat ekstrim dan hampir merata di seluruh wilayah Indonesia, berakibat meningkatnya risiko Demam Berdarah Dengue (DBD). Data dari laporan Kementerian Kesehatan (Kemenkes) mengenai kasus DBD di awal tahun 2019 menyatakan bahwa sejumlah wilayah di Indonesia sudah ditetapkan sebagai Kejadian Luar Biasa (KLB) DBD.…”
unclassified